What is Bottom-Up and What is Top-Down in Predictive Coding? - Rauss, Karsten; Pourtois, Gilles (Frontiers in Psychology, 2013)
Everyone knows what bottom-up is, and how it is different from top-down. At least one is tempted to think so, given that both terms are ubiquitiously used, but only rarely defined in the psychology and neuroscience literature. In this review, we highlight the problems and limitations of our current understanding of bottom-up and top-down processes, and we propose a reformulation of this distinction in terms of predictive coding.